BEHAVIORS OF FIELD SOILCRETE CREATED BY A LIGHT WEIGHT EQUIPMENT SYSTEM TO REINFORCE AN EARTH LEVEE IN VIETNAM (Malaysian Journal of Civil Engineering, 2018)
The current techniques reinforcing earth levees in the Mekong Delta have been less effective. The soil cement deep mixing technology (SCDM) using a small light weight equipment system has high potential to reinforce earth levees effectively and sustainably due to utilization of the in-situ soils. This paper investigated characteristics of field soilcrete created by a small light weight equipment system known as the NSV system in Dong Thap province which is one of thirteen provinces in the Mekong Delta. A 30-m soilcrete wall was completely constructed using the NSV in Dong Thap province. A 0.5-m thick wall of single row soilcrete columns and a 1-m thick wall of double row soilcrete columns with a depth of 8 m were built in 15 m long. Unconfined compressive strength test (UCS) was employed to determine the strength and stiffness of soilcrete specimens. About 60 soilcrete specimens were successfully made and tested using a UCS instrument in laboratory. Unconfined compressive strength, qu, inside a soilcrete column was higher than those of the designed strength about 4 to 5 times. The qu of 2-column overlapped locations was higher than those of inside columns about 1.6 to 2.5 times. The qu of 3-column overlapped locations was lower than those of inside columns about 1.4 to 1.6 times. Ratio of secant modulus of elasticity to UCS is about 28 to 140 times.